Tinjauan hukum positif dan hukum Islam terhadap keputusan Childfree pasangan suami istri - Maulidina, Annaafi (Maliki Interdisciplinary Journal, 2024)
The decision to live Childfree in Indonesia is not yet regulated by law. Nonetheless, this decision remains a subject of debate. Human rights, including the right to make this choice, have been regulated in Law No. 39/1999, which protects individuals' private rights, including sexuality and reproductive rights. However, religious views also influence society's views towards childfree, with some interpretations of the Qur'an emphasizing the importance of having legitimate offspring from marriage. Imam al Gazali highlighted that the reasons behind the decision not to have children can influence whether the act is considered halal or haram. If the reasons stem from well-founded concerns, such as disrupting children's lives or careers, then the decision is acceptable. However, if it is influenced by a wrong or discriminatory view of children or women, the decision may be considered inappropriate. Thus, while going childfree is still a matter of debate, the circumstances and reasons behind the decision should be carefully considered. Therefore, the author will examine the childfree decision of married couples in Indonesia, which is reviewed based on positive law and Islamic law.